2011
DOI: 10.2215/cjn.03340410
|View full text |Cite
|
Sign up to set email alerts
|

Low Physical Activity and Risk of Cardiovascular and All-Cause Mortality in Renal Transplant Recipients

Abstract: SummaryBackground and objectives Low physical activity (PA) is a risk factor for mortality in the general population. This is largely unexplored in renal transplant recipients (RTRs). We studied whether PA is associated with cardiovascular and all-cause mortality in a prospective cohort of RTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 48 publications
(43 reference statements)
3
120
0
3
Order By: Relevance
“…Lower scores for physical activity were associated with all-cause mortality, as well as death with a functioning graft. These data are consistent with data from other studies that demonstrate a relationship between physical functioning and outcomes after transplant (13,14). However, there is no consensus on what constitutes adequate physical functioning.…”
supporting
confidence: 88%
“…Lower scores for physical activity were associated with all-cause mortality, as well as death with a functioning graft. These data are consistent with data from other studies that demonstrate a relationship between physical functioning and outcomes after transplant (13,14). However, there is no consensus on what constitutes adequate physical functioning.…”
supporting
confidence: 88%
“…Recently, Zelle et al [8] using a different PA questionnaire found a strong association between low PA and all-cause mortality in prevalent KTRs who were transplanted at least a year earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Since PASE scores were not normally distributed, we created tertiles of PA, stratified by gender as per other reports [8]. We determined associations between PASE tertile and other participant attributes using ANOVA for continuous variables or χ 2 for categorical variables.…”
Section: Methodsmentioning
confidence: 99%
“…Following a kidney transplant, RTRs spontaneously increase their activity levels and this peaks at oneyear posttransplantation despite an initial decrease in the first month postoperatively [110] . Those who are more physically active have a reduced CV risk [111] and exercise programmes designed for RTRs have been shown to improve a number of physiological and psychological parameters [112,113] . However, blood pressure has been measured in several studies and there are no overall significant effects of exercise [114,115] .…”
Section: Lifestyle Factorsmentioning
confidence: 99%